Deregulated expression of Cdc6 as BCR/ABL-dependent survival factor in chronic myeloid leukemia cells - Jia-Hua Zhang; Yan-Li He; Rui Zhu; Wen Du; Jun-Hua Xiao (Tumor Biology)
Chronic myeloid leukemia is characterized by the presence of the reciprocal translocation t(9;22) and the BCR/ABL oncogene. The BCR/ABL oncogene activates multiple signaling pathways and involves the dysregulation of oncogenes during the progression of chronic myeloid leukemia. The cell division cycle protein 6, an essential regulator of DNA replication, is elevated in some human cancer cells. However, the expression of cell division cycle protein 6 in chronic myeloid leukemia and the underlying regulatory mechanism remain to be elucidated. In this study, our data showed that cell division cycle protein 6 expression was significantly upregulated in primary chronic myeloid leukemia cells and the chronic myeloid leukemia cell line K562 cells, as compared to the normal bone marrow mononuclear cells. BCR/ABL kinase inhibitor STI571 or BCR/ABL small interfering RNA could significantly downregulate cell division cycle protein 6 messenger RNA expression in K562 cells. Moreover, phosphoinositide 3-kinase/AKT pathway inhibitor LY294002 and Janus kinase/signal transducer and activator of transcription pathway inhibitor AG490 could downregulate cell division cycle protein 6 expression in K562 cells, but not RAS/mitogen-activated protein kinase pathway inhibitor PD98059 had such effect. Cell division cycle protein 6 gene silencing by small interfering RNA effectively resulted in decrease of proliferation, increase of apoptosis, and arrest of cell cycle in K562 cells. These findings have demonstrated that cell division cycle protein 6 overexpression may contribute to the high proliferation and low apoptosis in chronic myeloid leukemia cells and can be regulated by BCR/ABL signal transduction through downstream phosphoinositide 3-kinase/Akt and Janus kinase/signal transducer and activator of transcription pathways, suggesting cell division cycle protein 6 as a potential therapeutic target in chronic myeloid leukemia.